Exploring thematic nightmare content and associated self-harm risk - Hochard, Kevin D.; Ashcroft, Sam; Carroll, Janine; Heym, Nadja; Townsend, Ellen (Wiley, 2017)
Nightmares have been shown to be robust predictors of self-harm risk, beyond depressive symptoms and hopelessness at times. However, few studies have investigated associations between nightmare content and increased self-harm risk. The present study explored associations of thematic nightmare content with history of self-harm, and risk of self-harm phenomena the morning following a nightmare. A mixed-method diary study was employed. Prospective nightmare reports were obtained from 72 participants. A total of 47 nightmare reports met inclusion criteria and were analyzed for themes using inductive thematic analysis. Chi-square and bootstrap Pearson’s correlation tests were performed to assess the associations between nightmare themes and self-harm history and risk of self-harm phenomena following a nightmare. ‘Powerlessness to Change Behavior’ was associated a history of self-harm engagement, whereas ‘Financial Hardship’ indicated reduced risk. Themes were not significantly associated with increased risk of self-harm phenomena following a nightmare. Content may be of use in detecting lifetime history of self-harm engagement particularly in populations where disclosure is seen as taboo. However, nightmare symptom severity remains better indicators of risk. Evidence for the utility of nightmare content in assessing immediate self-harm risk is presently lacking. Replication with increased power is recommended.